El exilio de Simón Bolívar - Santana-Hernández, Adalberto (2017)
Exile marks the course of various political moments mostly in all Latin American countries. Throughout different stages of the Latin American and Caribbean history, exile has been a condition and a policy in which the subject banished it has had to leave his country to settle in another in this paper we discuss and identify the political exile of the Latin American forefather, Simón Bolívar. We analyze his actions in Curaçao, Jamaica and Haiti.